Thermo-mechanical low-cycle fatigue-creep of Haynes 230. (November 2017) - Ahmed, Raasheduddin; Barrett, Paul Ryan; Menon, Mamballykalathil; Hassan, Tasnim
Highlights: Developed a broad set of thermo-mechanical fatigue-creep (TMFC) responses of a superalloy. Demonstration of the influence of TMFC loading on mean stress evolution. Demonstration of the influence of TMFC loading on the elastic modulus rate change. Discussion on the challenges in constitutive model development for TMFC responses. Comparison of isothermal and thermo-mechanical fatigue-creep lives. Abstract: Combustor liners of airplane gas turbine engines experience premature thermo-mechanical fatigue-creep (TMFC) failure under operational loading conditions. The loading history of combustor liners encompass temperature fluctuation between ambient to as high as 1000 °C, and concurrent strain or stress fluctuation with load peak dwell-periods of 30 min to as long as 16 h of flying time. Repetition of such an anisothermal loading history leads to crack initiation in components via TMFC damage accumulation processes. In an effort to investigate such TMFC failures, a set of anisothermal experiments, both in-phase and out-of-phase, with peak dwell periods, were carried out for Haynes 230, a nickel-based superalloy used in constructing combustor liners. Analysis of the responses from out-of-phase experiments with compression dwells show mean-stress evolution in the tensile direction, while that from in-phase experiments with tensile dwells show mean-stress evolution in the compression direction. The total stress relaxation during peak strain dwell in the TMFC loading in general decreases with cycle, whereas that in the isothermal low-cycle fatigue-creep (LCFC) increases with cycle. The cyclic hardening-softening response is found to depend on the maximum temperature in the TMFC loading cycle. While calculating the inelastic strain in the experiments, it was found that the time derivative of the elastic modulus needed to be considered to prevent anomalous shifting of the hysteresis loops with cycles. The fatigue lives in the TMFC experiments are adversely affected by higher maximum temperatures and longer dwell-periods. These experimental responses are presented and analyzed, and challenges in developing a unified constitutive model for simulation of these responses are identified.